A Review on Dyslipidemia: Types, Risk Factors and Management - Purva, Arushi; Sharma, Kalpesh; Khan, Mohd. Shahid (Asian Journal of Pharmaceutical Research and Development, 2020)
Dyslipidemia is characterized by abnormally elevated cholesterol or fats (lipids) in the blood. Cardiovascular disease (CVD) is becoming more prevalent worldwide and is one of the leading causes of death. Dyslipidemia is an important risk factor for cardiovascular disease other factors are hypertension, diabetes mellitus, and smoking. Presently statins and fibrates are the major anti-hyperlipidemic agents for the treatment of elevated plasma cholesterol and triglycerides respectively, with remarkable side effects on the muscles and the liver.Lifestyle interventions remain a key component for the management of dyslipidemias. The present review will highlights types, risk factors and management available for dyslipidemia.